Identification of transforming growth factor beta family members present in bone-inductive protein purified from bovine bone. - Celeste, A J (1990)
Characterization of the polypeptides present in bone-inductive protein extracts from bovine bone has led to the cloning of seven regulatory molecules, six of which are distantly related to transforming growth factor beta. The three human bone morphogenetic proteins (BMPs) we describe herein, BMP-5, BMP-6, and BMP-7, show extensive sequence similarity to BMP-2, a molecule that by itself is sufficient to induce de novo bone formation in vivo. The additive or synergistic contribution of these BMP-2-related molecules to the osteogenic activity associated with demineralized bone is strongly implicated by the presence of these growth factors in the most active fractions of highly purified bone extract.